One size does not fit all. A non-linear analysis of European monetary transmission - Giulio Cifarelli; Giovanna Paladino (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2014)
This paper investigates the interest rate pass-through in eight European countries analyzing their short-run and long-run monetary transmission mechanisms. We investigate the relationship between the Euribor and the long-run interest rate on loans to non-financial corporations and allow for a mark-up which can be affected by country specific funding conditions and/or stochastic structural breaks. We detect significant differences across countries. Cointegration between the Euribor and the long-term bank loan interest rates holds for Germany, France, and the Netherlands, where banks seem to apply a constant mark-up. In the remaining countries of the sample the long-run pass-through is directly affected by changes in banks' cost of funding, due to shifts in the spread between domestic and German long-term government bond interest rates. The selection of the country specific ESTAR/LSTAR parameterization of the short-run dynamics detects a high degree of heterogeneity. The transition variables vary from the government bond spreads, in countries which were involved in the European debt crisis via sovereign bond market contagion, to the VXO index and to the Euribor monthly volatility.
Keywords: E43; E52; F36; C32; 330; Interest rate pass-through; Cointegration; ESTAR/LSTAR parameterization; EMU